Examining technology readiness constructs: A validation study - Ali, B.; Nawanir, G.; Nasidi, Y.; Bamgbade, Jibril Adewale (Akademia Baru, 2016)
This study validates technology readiness (TR) constructs in the context of public sector higher education institutions (HEIs) of Sultanate of Oman.Using a structured self ministered questionnaire, the data was duly collected from three hundred and thirty four educationists ranking from assistant lecturers to full professors.While employing PLS-SEM technique, the data was analyzed using Smart-PLS 2.0 M3 software. Results of this study revealed that all the dimensions of technology readiness namely; optimism, innovativeness, discomfort and insecurity were highly relevant.It also established an adequate level of internal consistency reliability, convergent validity and discriminant validity for each of the constructs of the technology readiness. Based on the results, it is suggested that the TR instrument could be useful for measuring all the constructs of technology readiness to study consumers’ tendency to adopt innovations or to accept the latest technologies.